Factors on Memory Retention: Effect to Students’ Academic Performance - Pillado, Irene A.; Futalan, Maria Chona Z.; Comighud, Sheena Mae T. (International Journal For Research In Mathematics And Statistics, 2020)
This paper examined the factors contributory to memory retention affecting the academic performance in mathematics of Grade 7 students of Kalumboyan High School, Bayawan City Division for SY 2019–2020. The study made use of the descriptive-correlational research design. The questionnaire covered five areas: motivational practices and experiences, goal setting and accomplishments, personalized learning, teaching strategies and learning activities, and educational resources and learning devices. The respondents of the study were the 160 Grade 7 students of Kalumboyan High School. The study utilized percentage, mean, weighted mean, and Spearman’s rank correlation coefficient. The salient findings revealed that the extent of students’ perception on factors contributory to memory retention were “high” in terms of motivational practices and experiences, goal setting and accomplishments, and personalized learning, while they perceived the use of teaching strategies and learning activities and the utilization of educational resources and learning devices to be “very high”. Moreover, the overall academic performance rating of the students in mathematics is at a fairly satisfactory level. Also, it can be concluded that the extent to which students perceived the factors contributory to memory retention is “very high” and has a moderate and significant relationship to their academic performance in mathematics.